Agent-Based Technologies and Applications for Enterprise Interoperability International Workshops, ATOP 2005, Utrecht, The Netherlands, July 25-26, 2005, and ATOP 2008, Estoril, Portugal, May 12-13, 2008, Revised Selected Papers - Fischer, Klaus; Müller, Jörg; Odell, James J. (Lecture Notes in Business Information Processing, 2009)
The ATOP (Agent-Based Technologies and Applications for Enterprise Interoperability) workshop series focuses on technologies that support interoperability in networked organizations, on successful applications of these technologies, and on lessons learned. So far two ATOP workshops have been held at the AAMAS conferences in Utrecht, The Netherlands, in July 2005, and in Estoril, Portugal, in May 2008. The 13 papers presented here are extended versions of carefully reviewed and selected contributions to the workshops. The topics covered are business interoperability; organizations and virtual institutions; modeling multiagent systems; agent interaction; and security. The main goal was to collect approaches for the application of agent technologies in these areas. Current trends in the development of agent technologies are compared with recent developments in service-oriented and model-driven system design, with respect to their ability to solve interoperability problems.